2011
DOI: 10.1002/cncr.26724
|View full text |Cite
|
Sign up to set email alerts
|

NRAS mutation status is an independent prognostic factor in metastatic melanoma

Abstract: BACKGROUND: There is a need for improved prognostic markers in melanoma. In this study, the authors tested the prognostic significance and clinicopathologic correlations of v-raf murine sarcoma viral oncogene homolog B1 (BRAF) and neuroblastoma RAS viral (v-ras) oncogene homolog (NRAS) mutations in patients with metastatic melanoma. METHODS: Clinical and pathologic data were collected retrospectively on melanoma patients who were clinically tested for BRAF (exon 15) and NRAS (exons 1 and 2) mutations at The Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
527
3
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 634 publications
(580 citation statements)
references
References 23 publications
36
527
3
14
Order By: Relevance
“…[11][12][13][14][15] These results have been recently confirmed by a retrospective analysis in a large cohort of patients with advanced melanoma who underwent testing for both BRAF (exon 15) and NRAS (exons 1 and 2) mutations. 5 Finally, it is important to underline that NRASQ61R has been reported to correlate with resistance to BRAF inhibitors in preclinical and clinical data. 8,16 Because testing for NRAS mutations currently requires the use of molecular techniques that are not available in most diagnostic pathology laboratories, testing may require a dispending laborious process before NRAS testing can commence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] These results have been recently confirmed by a retrospective analysis in a large cohort of patients with advanced melanoma who underwent testing for both BRAF (exon 15) and NRAS (exons 1 and 2) mutations. 5 Finally, it is important to underline that NRASQ61R has been reported to correlate with resistance to BRAF inhibitors in preclinical and clinical data. 8,16 Because testing for NRAS mutations currently requires the use of molecular techniques that are not available in most diagnostic pathology laboratories, testing may require a dispending laborious process before NRAS testing can commence.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the largest single-institution cohort of melanoma patients characterized for activating BRAF and NRAS mutations, the most common NRAS mutation was represented by the glutamine to arginine substitution at position 61 (NRASQ61R). 5 NRAS has so far proven to be intractable to conventional drug discovery, and several different strategies of directly targeting RAS have not resulted in effective therapeutics. Nevertheless, there is evidence that some NRASQ61R-mutated cell lines are sensitive to MEK inhibition in vitro.…”
mentioning
confidence: 99%
“…A subset of this cohort was published in 2012. 10 Genomic DNA was isolated from formalin-fixed, paraffinembedded tissue sections using a PicoPure DNA extraction kit (Life Technologies, Carlsbad, CA). Microscopic glass slide tissue sections were used.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that about half patients with advanced melanoma have BRAF mutation, and in some studies the mutation rate even reaches as high as 60% 88. Actually, the occurrence of BRAF mutations increases the risk of BM at first diagnosis of metastatic disease 89. It is well‐known that V600E is the most common mutation in BRAF which leads to the MAPK signaling pathway aberrantly activated 90.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%